The impact of library automation on the library staff and library services of EDSOR consortium schools - Gabiola, April M. (2002)
Computers have been present in the libraries since its introduction to offices in the early 1990s. Most of today's academic libraries already shifted to automation. School libraries, on the other hand are not being left behind. Numerous studies were done with regards to the impact of automation on the users of a library and only a few focused on the library personnel. It is in this light that his study centered on how library automation affects the library staff of three of the EDSA-Ortigas Consortium Schools - Immaculate Conception Academy, La Salle Greenhills, and Xavier School.